(untitled) (The International Journal for Scientific Research, 2023)
Based on several applied models, this study attempts to dismantle the structure of verbal interaction in its types: dialogues, conversations, discussions, interviews, in imaginary models represented in Aisha Al-Basri’s novel titled “Ka Jothatin fi riwayatin boulisyatin”, and a realistic one that took place between participants in the period of horrific events of Corona (Covid19) that has spread all over the world and shocked the entities of peoples. Contemporary man must do his self-reviews; socially, scientifically, cognitively, religiously, and politicly. When dialogue was the reliance on facing those challenges imposed by reality, the crisis became complicated on the social, political, economic, and linguistic levels, because laws of discourse were violated and didn’t consider the context of communication, which created a disruption in misunderstanding and a failure in education, because of the need of dialogue tools and etiquette of language, lexicon, style, and context, etc... This reality necessitated a pragmatic treatment, somehow it did this study, to restore what was lost and to remedy what the interventionists and mediators failed to solve the tension in the interrelationships in human society and further consolidate the language of dialogue, consensus, and harmony among human beings.